ASSESSMENT OF LEVEL OF COMPLIANCE WITH HEALTH AND SAFETY REGULATIONS ON NIGERIAN CONSTRUCTION SITES - Adakole Edwin, Agbo; Calistus , Ayegba (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Compliance with health and safety rgulations (H.S.R) on construction site is foundamental to employees’ safe delivery of work or assignment. The effectiveness of H.S.R on construction site leads to safe working condition which will increase efficiency and productivity. The study investigates levels of compliance of contractors, employees and clients with health and safety regulations on construction sites and the factors affecting compliance with H.S.R in Northern Nigeria. The study uses physical observation on site with check list and questionnaire to generate data used. The analysis of data was done by the use of SPSS spread sheet to obtain mean scores. The result indicated that employers/contractors’ level of compliance was little, while employees comply averagely and clients show a high compliance level. Lack of contract provision to support compliance with H.S.R., bribery and corruptions, lack of enforcement, management negligent attitude and lack of knowledge on H.S. policy implementation were identified and ranked by the respondents as the 5 top most critical factors affecting compliance with H.S.R on construction site in Northern Nigeria. The study concluded that compliance level of employers/contractors with H.S.R on construction sites in Northern Nigeria was low. It is recommended that provision for H.S. in contract document be made and severe penalties be attached to non compliance with H.S.R on construction site.